Unbiased profiling of volatile organic compounds in the headspace of Allium plants using an in-tube extraction device - Kusano, Miyako (BMC Res Notes, 2016)
BACKGROUND: Plants produce and emit important volatile organic compounds (VOCs), which have an essential role in biotic and abiotic stress responses and in plant–plant and plant–insect interactions. In order to study the bouquets from plants qualitatively and quantitatively, a comprehensive, analytical method yielding reproducible results is required. RESULTS: We applied in-tube extraction (ITEX) and solid-phase microextraction (SPME) for studying the emissions of Allium plants. The collected HS samples were analyzed by gas chromatography–time-of-flight–mass spectrometry (GC-TOF–MS), and the results were subjected to multivariate analysis. In case of ITEX-method Allium cultivars released more than 300 VOCs, out of which we provisionally identified 50 volatiles. We also used the VOC profiles of Allium samples to discriminate among groups of A. fistulosum, A. chinense (rakkyo), and A. tuberosum (Oriental garlic). As we found 12 metabolite peaks including dipropyl disulphide with significant changes in A. chinense and A. tuberosum when compared to the control cultivar, these metabolite peaks can be used for chemotaxonomic classification of A. chinense, tuberosum, and A. fistulosum. CONCLUSIONS: Compared to SPME-method our ITEX-based VOC profiling technique contributes to automatic and reproducible analyses. Hence, it can be applied to high-throughput analyses such as metabolite profiling. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13104-016-1942-5) contains supplementary material, which is available to authorized users.